Pengembangan Deteksi Spesifik untuk Mungbean Yellow Mosaic India Virus yang Menginfeksi Kacang Panjang di Jawa, Indonesia - Nurulita, Sari; Mutaqin, Kikin; Hidayat, Sri (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
Yellow mosaic disease was reported for the first time in Indonesia in 2008. Its infection on yard long bean caused significant yield loss. Mungbean yellow mosaic India virus (MYMIV), member of genus Begomovirus was identified as the main causal agent. Specific and accurate detection is important for disease monitoring as part of disease management strategy. The aim of this study was to construct specific primer pairs for quick and robust detection of MYMIV using polymerase chain reaction method. A pair of primers MY1/MY2 was designed in this study to amplify part of MYMIV coat protein. In silico and in vitro test showed that MY1/MY2 primers specifically amplified MYMIV.